Mechanisms of NLRP1-Mediated Autoinflammatory Disease in Humans and Mice. Issue 2 (19th January 2018) - Yu, Chien-Hsiung; Moecking, Jonas; Geyer, Matthias; Masters, Seth L.
Abstract: NLRP1 was the first NOD-like receptor described to form an inflammasome, recruiting ASC to activate caspase-1, which processes interleukin-1β and interleukin-18 to their active form. A wealth of new genetic information has now redefined our understanding of this innate immune sensor. Specifically, rare loss-of-function variants in the N-terminal pyrin domain indicate that this part of NLRP1 is autoinhibitory and normally acts to prevent a familial autoinflammatory skin disease associated with cancer. In the absence of a ligand to trigger human NLRP1, these mutations have now confirmed the requirement of NLRP1 autolytic cleavage within the FIIND domain, which had previously been implicated in NLRP1 activation. Autolytic cleavage generates a C-terminal fragment of NLRP1 containing the CARD domain which then forms an ASC-dependent inflammasome. The CARD domain as an inflammasome linker is consistent with the observation that under some conditions, particularly for mouse NLRP1, caspase-1 can be engaged directly, and although it is no longer processed, it is still capable of producing mature IL-1β. Additional rare variants in a linker region between the LRR and FIIND domains of NLRP1 also cause autoinflammatory disease in both humans and mice. This new genetic information is likely to provide for more mechanistic insight in the years to come, contributing to our understanding of how NLRP1 functions as an innate immune sensor of infection and predisposes to autoimmune or autoinflammatory diseases. Graphical abstract: Highlights: Genetic variants in NLRP1 lead to autoimmune and autoinflammatory diseases in both humans and mice. NLRP1 N-terminal domain (PYD in humans) is autoinhibitory, whereas the C-terminal cleavage fragment containing the CARD domain engages an ASC-dependent inflammasome. Disease-associated mutations in the NLRP1 linker region between NACHT and LRR domains suggest additional mechanisms of autoinhibition.